Zimora - um modelo numérico 3D de dispersão atmosférica - Zimermann, Hans Rogério (2009)
In this thesis, we presents a development and validation of a 3D numerical model for the advection-diffusion equation. Models of this kind has been developed for scientific investigations and to support atmospheric emissions control and environmental policy decisions. To develop this model, we used the computational implementation of an explicit numerical scheme for the discretization of the envolved equations. During this procedures, exaustive tests were performed to ensure that the used implementations agrees to the stability, consistence and convergence criterias. As a way for minimizing one of the main deficiences found in almost the major atmospheric dispersion models, i.e. imprecisions in the meteorological input data for initializing this models, we used a realistic atmospheric flow field generated by mesoscale circulation model. As the mesoscale model gives information at scale larger than the necessary for description of a plume trajectory, a weighted linear average proper interpolation was developed for intermediate these distances. Our model considers the assumption that atmospheric turbulence is not isotropic, where diffusion coefficients are variables in time and space and are different for lateral and vertical directions. In our model we estimate this coefficients by the atmospheric boudary layer parameterizations proposed byMoraes (2000). For validation of themodel, we used experimental datasets from field experiment carried near a thermoelectric power plant presidente Médici, in the city of Candiota/RS. These datasets contains surface SO2 concentrations, surface wind velocity measured in meteorological towers as well as turbulence data measured in micrometeorological towers. The results of the validation indicates that the model works well, at least for the source and the terrain were it is located. i.e. continuous emission and homogeneous topography.